Illustrated Classic : Pinocchio - Collodi, Carlo, 1826-1890; Vavouri, Elsa (Essex, United Kingdom : Miles Kelly Publishing Ltd., 2018)
Delightfully written, Pinocchio follows the exciting adventures of a mischievous wooden puppet who wants to become a boy. With a stunning foiled jacket, ribbon marker and beautiful original colour illustrations throughout, this is a book to treasure.
Keywords: Pinocchio (Fictitious character) -- Pictorial works -- Juvenile fiction; Children's stories, English; Folk literature, English